An extensible network slicing framework for satellite integration into 5G. (12th November 2020) - Drif, Youssouf; Chaput, Emmanuel; Lavinal, Emmanuel; Berthou, Pascal; Tiomela Jou, Boris; Grémillet, Olivier; Arnal, Fabrice
Summary: With the imminent deployment of the 5th generation (5G) mobile network in the nonstand‐alone version, some researches focus on network slicing to fully exploit the 5G infrastructure and achieve a highest level of flexibility in the network. This level of flexibility offered by the network slicing paradigm also fits the need of satellite networks in which satellite network operators (SNOs) want to offer 5G connectivity services additionally to the traditional satellite connectivity. However, the work that has been done so far for network slicing in 5G does not directly apply to satellite networks due to satellite architecture specificities and thus needs to be extended. We extend the work on network slicing and this paper proposes a novel Satellite Slicing Framework in order to fully exploit the satellite infrastructure and to facilitate the integration of satellite services into 5G. Our framework includes defining, modeling, orchestrating, and deploying multiple satellite network slices and their associated network services on top of mutualized satellite infrastructures. Abstract : In this paper, we confront the challenges related to the network slicing paradigm with the satellite network and define precisely what a satellite slice is. We take a top‐down approach to design an extensible network slicing framework in order to facilitate 5G end‐to‐end service delivery though an integrated satellite and terrestrial network. In particular, we propose a more flexible satellite network architecture relying on key enablers such as SDN/NFV paradigms to allow further coordination between satellite and terrestrial systems.